The microbiological features and risk factors for liver abscess after thermal ablation of liver cancer - Ding, Xiurong; Yu, Yanhua; Chen, Ming; Kang, Yanfang; Lou, Jinli (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesLiver abscess is a severe complication that can occur following thermal ablation of liver cancer, with an incidence rate ranging from 0.2% to 2.4%. This study aimed to identify risk factors associated with the development of post-ablation liver abscesses and to characterize the microbiological features of the isolated pathogens.MethodsA matched case-control study was conducted at Beijing Youan Hospital from January 2018 to December 2023. Cases were defined as patients who developed liver abscesses within three months following ablation therapy, while controls comprised patients who did not develop such abscesses. Clinical and microbiological data were collected and analyzed. The relevant independent risk factors for the occurrence of liver abscesses were identified and assessed using multivariate logistic regression analysis.ResultsPost-ablation liver abscesses predominantly occurred in male patients aged 60 years or older, typically manifesting around six days after the procedure. Common symptoms included fever, chills, abdominal distension, and abdominal pain. Multivariate analysis identified diabetes mellitus (OR=3.215; 95% CI 1.330–7.771), history of abdominal surgery (OR=2.810; 95% CI 1.074–7.353), biliary disease (OR=18.832; 95% CI 2.291–154.795), and elevated ALP levels (OR=1.010; 95% CI 1.002–1.019) as independent risk factors for post-ablation liver abscesses. Among the 61 patients with liver abscesses, a total of 78 bacterial strains were isolated from the abscess fluid, with Gram-negative bacteria accounting for 75.6% of the isolates. Escherichia coli (30.8%) and Klebsiella pneumoniae (20.5%) were the most frequently identified pathogens. Drug sensitivity testing revealed that both Escherichia coli and Klebsiella pneumoniae exhibited high susceptibility to Amikacin, Cefoxitin, Ceftazidime, Imipenem, Meropenem, and Piperacillin-tazobactam.ConclusionsPost-ablation liver abscesses are primarily caused by Gram-negative bacteria. A history of diabetes, prior abdominal surgery, biliary disease, and elevated ALP levels are significant risk factors influencing the development of post-ablation liver abscesses.